Effect of Physical Activity and Nutrition Education Module on Physical Health, Mental Health and Dietary Habits of Secondary School Students in Khyber- Pakhtunkhwa Pakistan - Amjad, Ali Khan (2024)
This study examined the effect of physical activity and nutrition education module on physical health, mental health and dietary habits of secondary school students in rural and urban areas of Khyber-Pakhtunkhwa, Pakistan. ADDIE Model was used to develop the physical activity and nutrition education module. A quasi-experimental approach was used to evaluate the effectiveness of the module. The interventional program was conducted for eight weeks. Data were collected from 60 participants before and after the 8 weeks of the intervention. A total of 30 participants were taken in each experimental and control group, which were further distributed by 15 from urban area and 15 from rural area. Physical Health Questionnaire (PHQ), Warwick-Edinburgh Mental Well-being Scale (WEMWBS) and Adolescent Food Habit Checklist (AFHC) was used to compare the physical health, mental health and dietary habits of the participants. Mann-Whitney U test and Wilcoxon Signed Ranks test utilized to achieve the objective of the study. The validity and useability of module was evaluated by panel of experts. The content validity index (CVI) was 0.9, indicate an exceptional degree of expert agreement for validity and useability. The homogeneity of the groups was confirmed before the intervention which yielded non- significant Mann-Whitney U statistics 402.50 with a p value of 0.482>0.05. Results showed that after the intervention the physical health, mental health and dietary habit of participants were significantly improved (p < 0.05), which confirmed the effectiveness of the module. The pre-post comparison of experimental and control group showed no significant change in physical health (p = 0.573), mental health (p =0.109) and dietary habit (p = 0.317) of participants in the control group, but a significant improvement was observed in the experimental group (p < 0.05). Finding also showed that the module was effective for student in urban and rural area (p < 0.05) and urban area have been improved significantly as compared to rural area. As a conclusion, this module effectively improved the physical health, mental health and dietary habits of secondary school students in Pakistan. The study implicates that physical activity and nutrition education modules can be used as a guideline to improve physical, mental and nutritional dietary habit among students.